Gluten specific suppressor T cell dysfunction in coeliac disease. Issue 4 (April 1986) - Corazza, G R; Sarchielli, P; Londei, M; Frisoni, M; Gasbarrini, G
Abstract : A T lymphocyte direct migration inhibition factor test has been used to investigate the function of the specific suppressor T cell population controlling the immune response to gluten in coeliac disease. The test has been carried out in 21 adult coeliac patients, 22 Mantoux- healthy controls and eight Mantoux+ donors using gluten fraction III and purified protein derivative, as antigens. All coeliacs, but two, were Mantoux-. When gluten fraction III was used a significant migration inhibition was observed in coeliac patients compared to controls; such migration inhibition was abrogated by coculturing in a 1:1 ratio coeliac T cells with T cells from controls or Mantoux+ donors. On the contrary, the addition to coeliac T cells of T lymphocytes from other coeliacs did not abolish migration inhibition to gluten. Pretreatment of normal T cells with mitomycin C prevented their abrogating activity on migration inhibition of coeliac T lymphocytes. When purified protein derivative was used as antigen a significant migration inhibition was observed in Mantoux+ donors compared with healthy subjects and such migration inhibition was abolished by co-culturing T cells from Mantoux+ donors with those from Mantoux- controls and coeliac patients. Our results show that coeliac T cells, while retaining their ability to suppress the immune response to purified protein derivative, cannot suppress the immune response to gluten and are consistent with the hypothesis that a gluten specific suppressor T cell dysfunction, rather than a generalised T lymphocyte defect, may play a role in the pathogenesis of coeliac disease.